2023
DOI: 10.1007/s00277-023-05170-0
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell mobilization in multiple myeloma: challenges, strategies, and current developments

Abstract: Among hematological malignancies, multiple myeloma (MM) represents the leading indication of autologous hematopoietic stem cell transplantation (auto-HCT). Auto-HCT is predominantly performed with peripheral blood stem cells (PBSCs), and the mobilization and collection of PBSCs are essential steps for auto-HCT. Despite the improved success of conventional methods with the incorporation of novel agents for PBSC mobilization in MM, mobilization failure is still a concern. The current review comprehensively summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…These cells may be accounted as hematopoietic progenitor cells by the XN‐20 module, which leads to diagnostic inaccuracy. A resulting tumor cell contamination of the graft could be expected in those cases 22 . A possible future investigation might examine whether a tumor cell contamination of the graft results in a poorer correlation of XN‐20 HPC measurement and flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be accounted as hematopoietic progenitor cells by the XN‐20 module, which leads to diagnostic inaccuracy. A resulting tumor cell contamination of the graft could be expected in those cases 22 . A possible future investigation might examine whether a tumor cell contamination of the graft results in a poorer correlation of XN‐20 HPC measurement and flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, auto-HSCT improved PFS, indicating its therapeutic status in newly diagnosed MM patients. 3 Besides, auto-HSCT is crucial for MM patients after transplantation, even if monoclonal antibody-containing regimens are used as induction therapy. 4 Furthermore, auto-HSCT is crucial for relapsed or primary refractory diffuse large B-cell lymphoma or high-grade B-cell lymphoma, refractory mantle cell lymphoma, and peripheral T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In one prospective study, it was found that all patients treated with six cycles of lenalidomide-based triplet therapy were able to collect enough cells for autologous transplant without mobilization failure [25] . Another analysis found that induction therapy with up to six cycles of VRD and KRD did not lead to stem cell mobilization failure [26] . Further, relaxing requirements of induction cycles prior to transplant can facilitate easier communication and workflow with community physicians referring patients to distant transplant centers and allow ongoing deep remissions in patients prior to transplant, which, as above, has been shown to be beneficial.…”
Section: Optimal Timing Of Mobilizationmentioning
confidence: 99%